2010
DOI: 10.1371/journal.pone.0015123
|View full text |Cite
|
Sign up to set email alerts
|

Nε−Lysine Acetylation of a Bacterial Transcription Factor Inhibits Its DNA-Binding Activity

Abstract: Evidence suggesting that eukaryotes and archaea use reversible N ε-lysine (N ε-Lys) acetylation to modulate gene expression has been reported, but evidence for bacterial use of N ε-Lys acetylation for this purpose is lacking. Here, we report data in support of the notion that bacteria can control gene expression by modulating the acetylation state of transcription factors (TFs). We screened the E. coli proteome for substrates of the bacterial Gcn5-like protein acetyltransferase (Pat). Pat acetylated four TFs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
147
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(153 citation statements)
references
References 51 publications
(97 reference statements)
5
147
1
Order By: Relevance
“…This notion was validated in the cases of the CheY and RcsB response regulators of E. coli [6] and [13], respectively). In the case of CheY, it was revealed by co-crystallization that certain lysine residues were directly involved in binding to DNA targets [27,28].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This notion was validated in the cases of the CheY and RcsB response regulators of E. coli [6] and [13], respectively). In the case of CheY, it was revealed by co-crystallization that certain lysine residues were directly involved in binding to DNA targets [27,28].…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, it appears that phosphorylated, that is, activated RprY is the preferred substrate for acetylation suggesting cross-talk between the protein modification activities. Finally, we show that acetylated RprY had diminished ability to bind to promoter DNA; thus, modification of regulator proteins by acetylation appears to be another mechanism to modulate their function [6], including derepression.…”
Section: Introductionmentioning
confidence: 99%
“…One such candidate is the transcription factor RcsB, which was reported to be deacetylated by CobB in E. coli and S. enterica. In this case, deacetylation of the RcsB protein was reported to lead to augmentation of its DNA-binding activity (Thao et al, 2010). Ma and Wood (2011) reported that protein deacetylation by CobB leads to a decreased resistance of E. coli against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In order to elicit such effects as probiotics, the bacteria need to survive gastric fluid and bile acid in the digestive canal of the host, and preferably to settle on appropriate sites. Regarding the application of LAB as a probiotic, it would be intriguing to find out which target proteins of LAB play a role in the survival against stress in host intestines (van de Guchte et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation